DISTURBANCES OF NUTRINIONAL STATUS IN PATIENTS TREATED BY PERITONEAL DIALYSIS: THE ROLE OF CHRONIC INFLAMMATION - Dudar, I.; Shymova, A.; Krasyuk, E. (Ukrainian Journal of Nephrology and Dialysis, 2017)
this work is devoted to the problem of malnutrition in patients who are treated by peritoneal dialysis, also the role of chronic inflammation was described.